Auditing farm animal refuge: management and welfare of livestock in disaster situations - Silva, Sillas M. S.; Del Valle, Cássia C. V.; Reis, Vanessa M.; Bonatto, Carolina R.; Fournier, Gislene F. S. R.; Bertelli, Felipe; Castro, Alex (Frontiers in Veterinary Science, 2025)
The collapse of mining dams in Brazil exposed significant deficiencies in emergency planning for livestock, resulting in prolonged vulnerability of cattle in disaster-affected areas. This study presents a pioneering initiative that implemented a temporary refuge for approximately 575 cattle, incorporating veterinary oversight, nutritional and reproductive management, and behavioral monitoring. The initiative was developed within the framework of the Fauna Term of Covenant, an institutional agreement that ensured independent technical auditing and legal accountability. This experience offers a replicable model for protecting livestock in socio-environmental crises. It also illustrates how veterinary and animal sciences intersect with governance, ethics, and environmental justice, emphasizing that effective animal welfare in disaster contexts requires more than technical solutions. It demands sustained institutional commitment and interdisciplinary collaboration. The findings contribute to the development of future frameworks for integrating production animals into emergency response and public policy.